2018
DOI: 10.4172/neuropsychiatry.1000226
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychological Efficacy of Vagus Nerve Stimulation in 56 Children with Catastrophic Epilepsy

Abstract: Background:For children with catastrophic epilepsy, vagus nerve stimulation has been demonstrated as a palliative treatment for those with surgical contraindication. The purpose of our study was to assess the efficacy on seizures, to assess the neuropsychological efficacy of vagus nerve stimulation in children. Methods:Our study reviewed files of 56 children treated with vagus nerve stimulation between May, 2008 and December, 2013 in our center. Data was collected from baseline to 12, 24 months of follow-up, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There is reason to believe that earlier treatment with non-pharmacological modalities will yield better cognitive functions in such children. Some reports in the literature addressed more improvement in cognitive domains in children < 6 years than those between the age of 6–14 years [51] . Other reports show no improvement of cognitive functions [52] .…”
Section: Discussionmentioning
confidence: 99%
“…There is reason to believe that earlier treatment with non-pharmacological modalities will yield better cognitive functions in such children. Some reports in the literature addressed more improvement in cognitive domains in children < 6 years than those between the age of 6–14 years [51] . Other reports show no improvement of cognitive functions [52] .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, cognitive deficits, or mental retardation, may be considered as one of most common comorbidities of refractory epilepsy, especially for children [3,33]. Our recent study has demonstrated that vagus nerve stimulation (VNS) or deep brain stimulation (DBS) might improve neuropsychological outcomes, including language, memory, perception [34,35]. Consequently, we hypothesize that VNS or DBS may be an alternative treatment for SWS patients with refractory epilepsy, especially for those who cannot receive surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-year follow-up after VNS showed a 60% rate of ≥50% seizure frequency reduction in a Korean study (mean age, 22.3 years; range, 8–44 years) [16]. Chinese colleagues retrospectively analyzed the effects of VNS on children (range, 1–14 years) and showed a 57.2% of patients experienced a ≥50% seizure frequency reduction [78]. A Japanese prospective study revealed a median seizure reduction of 66.2% after 3 years of VNS [42].…”
Section: Clinical Outcomesmentioning
confidence: 99%